THE EFFECTS OF AESTHETIC VALUE IN FOOD AND BEVERAGE BUSINESSES ON THE AESTHETIC EXPERIENCES AND REVISIT INTENTIONS OF CUSTOMERS - Çağrı SÜRÜCÜ (Fırat University, 2019)
This study presents the effect of aesthetic value of food and beverage businesses on aesthetic experiences of the customers and their revisit intentions. According to the established study model, firstly aesthetic value components of the restaurants were determined and the effect of aesthetic value on aesthetic experiences was revealed. Then, the influence of aesthetic value and aesthetic experience upon revisit intentions of the customers was tested through hypotheses. This study was conducted in luxury restaurants and 1st and 2nd class restaurants located in Mugla city center, Milas, Bodrum, Marmaris, Datça, Dalaman and Fethiye with tourism operation licenses. For the analyses of the obtained data, absolute and percentage value, factor analysis, simple regression and multiple regression analyses were applied. According to the results, it was determined that there was a positive significant relationship between aesthetic value of restaurants and aesthetic experiences of customers and that positive aesthetic value and aesthetic experiences increased revisit intentions of customers. In this way, details like colors, lighting or objects which are known to have an influence upon customers’ perceptions and mood can be used in an aesthetic way that customers can gain positive aesthetic experiences. Thus, by increasing revisit intentions of customers, restaurants can obtain a competitive advantage.